H2O/O2 Vapor Annealing Effect on Spin Coating Alumina Thin Films for Passivation of Silicon Solar Cells - Abdullah Uzum (International Journal of Photoenergy, 2019)
Aluminum acetylacetonate-based AlOx thin films were introduced as a low-cost, high-quality passivation layers for crystalline silicon solar cells. Films were formed by a spin coating method on p-type silicon substrates at 450°C in ambient air, O2, or water vapor (H2O/O2) for 15 or 120 min. XPS analysis confirms the AlOx formation and reveals a high intensity of interfacial SiOx at the AlOx/Si interface of processed wafers. Ambient H2O/O2 was found to be more beneficial for the activation of introduced AlOx passivation films which offers high lifetime improvements with a low thermal budget. Carrier lifetime measurements provides that symmetrically coated wafers reach 119.3 μs and 248.3 μs after annealing in ambient H2O/O2 for 15 min and 120 min, respectively.